Improving Students’ Writing Skill Using Virtual Writing Tutor: Automatic Corrective Feedback - Viantika, Salma; Dangin, Dangin (EDULIA: English Education, Linguistic and Art Journal, 2024)
Technological advances are becoming a superior approach in the world of learning and education. Technology plays an important role in developing improved learning outcomes which are used as media or learning aids. The problem found was the low quality of students' writing skills, after observations students received assessments or feedback that were not detailed. Therefore, the research is to improve the quality of students' writing using the AI-based Virtual Writing Tutor platform. The study uses Classroom Action Research as a research design which is carried out cyclically in teaching research and is followed by increasing participant data results. This research involved 32 class XI students of Indonesian Senior High School for the 2023/2024 academic year. This research found that Virtual Writing Tutor can help improve students' writing performance. This can be seen through the average score which increased from the pre-test, starting from an average of 52.9, then increased in the progress-test to produce 63.2 and increased up to 75.6 in post-test. To find out responses from participants, interviews were conducted with a focus on strengths and weaknesses. Then, from the interview results, it was concluded that there were good impacts and bad impacts on the use of AI-based platforms. Keywords: Automatic Corrective Feedback, Virtual Writing Tutor, Writing Skill